If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -12x + 6x = 64 Combine like terms: -12x + 6x = -6x 8 + -6x = 64 Solving 8 + -6x = 64 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -6x = 64 + -8 Combine like terms: 8 + -8 = 0 0 + -6x = 64 + -8 -6x = 64 + -8 Combine like terms: 64 + -8 = 56 -6x = 56 Divide each side by '-6'. x = -9.333333333 Simplifying x = -9.333333333
| 3r+3-5=3r-2 | | f(x)=-3-8 | | 16k^2+122k=-70 | | 3X^3-X^2-30X=0 | | log(11-x)=.5 | | 8(28)= | | f(-2)=-3x-8 | | 6x-8=2x+1 | | 49+7x=21 | | 2ln(x)-ln(2x-5)=ln(7x)-ln(x+2) | | 300*.10=5 | | 10x+4-2x=8 | | 4cotx+1=5 | | 2400-160x+2x^2=1312.5 | | 7r^2+5r+3=0 | | 8s^2-22s+5=0 | | (x+0.5)(x+3.4)=0 | | 2.16b+5=1.6b+10 | | 144= | | 144=12 | | 2(2z-2)-2(4-2z)=2 | | 3x+15+39=90 | | 12r^2+3=0 | | 3x+15+39=180 | | 7x-16=-1 | | 8-3=10y | | -2x+1-(-3x+3)=-4+(-x-2) | | 0.8=0.2y+3.4 | | 5t-23=-23+7t | | 9x+19=-26 | | -3p-5-p-(-3p)+4p+7p+5= | | 4x^3-40x^2+96x=0 |